Influence of the endodontic access cavity design and restorative technique on hard tissue removal and fracture resistance of mandibular premolars (Research, Society and Development, 2022)
This study assessed the influence of traditional (TradAC) and conservative access (ConsAC) with different restorative techniques on the percentage of hard tissue removed (%HTR) and on the fracture resistance of mandibular premolars. 45 premolars were scanned in a micro-computed tomography and assigned into four groups according to access (TradAC or ConsAC) and restorative technique: composite resin (CR) or fiber post (FP) + CR. After post preparation, the teeth were rescanned to determine the volume enlargement and %HTR from the crown and root canal. After restoration, the load at fracture was recorded. Data were analyzed statistically by one-way ANOVA and Tukey’s post-hoc test, ANOVA repeated measure, and chi-square tests (P